ETAS: An R Package for Fitting the Space-Time ETAS Model to Earthquake Data - Abdollah Jalilian (Journal of Statistical Software, 2019)
The epidemic-type aftershock sequence (ETAS) model is the most widely used statistical model to describe earthquake catalogs. ETAS is an R package for fitting the space-time ETAS model to an earthquake catalog using the stochastic declustering approach introduced by Zhuang, Ogata, and Vere-Jones (2002). The package provides two classes and several functions to facilitate data preparation, model fitting and some simple diagnostic checks. The present paper is a description of the package and illustrates modeling earthquake data using the space-time ETAS model.